Enhanced H3K4 Trimethylation in TNF-α Promoter Gene Locus with Cell Apoptosis in the Ventral-Medial Striatum following Opioid Withdrawal of Neonatal Rat Offspring from Morphine-Addicted Mothers - Pei-Ling Wu; Jau-Ling Suen; Chun-Hwa Yang; Kuang-Che Kuo; Yu-Chen S. H. Yang; San-Nan Yang (Mediators of Inflammation)
Prenatal opioid exposure might disturb epigenetic programming in the brain of neonatal offspring with various consequences for gene expressions and behaviors. This study determined whether altered trimethylation of histone 3 at lysine 4 (H3K4me3) in the promoter of the tumor necrosis factor-α (tnf-α) gene with neural cell apoptosis was involved in the ventral-medial striatum, an important brain region for withdrawal symptoms, of neonatal rat offspring from morphine-addicted mothers. Female adult rats were injected with morphine before gestation and until 14 days after giving birth. On postnatal day 14 (P14), rat offspring from morphine-addicted mothers were subjected to an opioid-withdrawal protocol and were analyzed 2 or 8 h after administration of that protocol. Expressions of the TNF-α protein, H3K4me3 in the tnf-α promoter gene, and neural cell apoptosis within the ventral-medial striatum of neonatal rat offspring were evaluated. In the absence of significant opioid withdrawal (2 h after initiation of the opioid-withdrawal protocol on P14), prenatal morphine exposure led to increased levels of H3K4me3 in the tnf-α promoter gene, of the TNF-α protein, and of neural cell apoptosis within the ventral-medial striatum of neonatal rat offspring. Following opioid withdrawal (8 h after initiation of the opioid-withdrawal protocol on P14), differential expression of H3K4me3 in the tnf-α promoter gene locus and upregulation of the level of TNF-α protein expression were further enhanced in these offspring. In addition, increased levels of caspase-3 and neural cell apoptosis were also observed. Taken together, this study revealed that prenatal opioid exposure can activate an epigenetic histone mechanism which regulates proinflammatory factor generation, which hence, led to cell apoptotic damage within the ventral-medial striatum of neonatal rat offspring from morphine-addicted mothers. More importantly, the opioid-withdrawal episode may provide augmented effects for the abovementioned alterations and could lead to deleterious effects in the neonatal brain of such offspring.